Income Mobility and Welfare - Tom Krebs; Pravin Krishna; William F. Maloney (University of Mannheim, Department of Economics, 2013)
This paper develops a framework for the quantitative analysis of individual income dynamics, mobility and welfare. Individual income is assumed to follow a stochastic process with two (unobserved) components, an i.i.d. component representing measurement error or transitory income shocks and an AR(1) component representing persistent changes in income. We use a tractable consumption-saving model with labor income risk and incomplete markets to relate income dynamics to consumption and welfare, and derive analytical expressions for income mobility and welfare as a function of the various parameters of the underlying income process. The empirical application of our framework using data on individual incomes from Mexico provides striking results. Much of measured income mobility is driven by measurement error or transitory income shocks and therefore (almost) welfare-neutral. A smaller part of measured income mobility is due to either welfare-reducing income risk or welfare-enhancing catching-up of lowincome individuals with high-income individuals, both of which have economically significant effects on social welfare. Decomposing mobility into its fundamental components is thus seen to be crucial from the standpoint of welfare evaluation.
urn:nbn:de:bsz:180-madoc-329284
Keywords: 330